Disputed Land, Contested Knowledge: Laying Ground for a Global Theory of Indigenous Reterritorializations across the Americas - Hirt, Irène (Swiss Journal of Sociocultural Anthropology, 2017)
This paper is a fi rst step towards theorizing indigenous reterritorializations across the Americas through a relational and contextual approach of indigeneity and territory. I argue that struggles for land, territory and natural resources come with the decolonization of knowledge and representations. While these processes are expressed through the mapping of territory and the rewriting of history, they are also inducing an evolving relationship between indigenous peoples and researchers towards collaborative research practices.